Planning a Systematic Way Out of Commodity Smuggling with Integrated Marketing Communications Management Approach (Case Study: Covid-19 Outbreak Crisis) - Hamed Riahi; Naser Azad; Tahmores Hasangholipor yasory; Kiamars Fathi Hafshejani (پژوهش‌های برنامه و توسعه, 2023)
Commodity smuggling is a complex phenomenon with multiple dimensions, which is related to the hidden and underground economy on the one hand, and to social order, cultures, and attitudes on the other hand. In the conditions of the spread of Covid-19 as a global crisis, the complexity of the situation of goods smuggling has increased. Getting out of the situation of smuggling as an economic disease and a critical situation that is considered as one of the country's development challenges, requires coordinated and integrated measures, and the approach of integrated marketing communications can be used to deal with such challenges. Therefore, planning a systematic way out of commodity smuggling with the integrated marketing communication management approach (case study: Covid-19  outbreak crisis) was proposed for the first time.The present exploratory research was presented through semi-structured interviews of 12 experts and using the database theory and the Delphi method, conceptual model and appropriate theory, extracting 18 categories and 82 sub-components, content validity (0.71), retest reliability (77%), and reliability two coders (65%) were evaluated favorably and practical suggestions were presented by documenting organizational knowledge.It seems that in the crisis of the Covid-19 outbreak, planning through the management of integrated marketing communications can be used to prevent and get out of the situation of smuggling of goods towards the health of the business environment and economic development.Therefore, planning a systematic way out of commodity smuggling with the integrated marketing communication management approach (case study: Corona outbreak crisis) was proposed for the first time.The present exploratory research was presented through semi-structured interviews of 12 experts and using the data base theory and the Delphi method, conceptual model and appropriate theory, while extracting 18 categories and 82 sub-components, content validity (0.71), retest reliability (77%) and reliability Two coders (65%) were evaluated favorably and practical suggestions were presented by documenting organizational knowledge.Among the categories, "supporting legal trade while modifying and completing the business model" and "supporting production while modifying and completing the production and employment model" had the highest frequency. It seems that in the crisis of corona outbreak, planning through the management of integrated marketing communications can be used to prevent and get out of the situation of smuggling of goods towards the health of the business environment and economic development.